Evaluation of fiber and debris release from protective COVID-19 mask textiles and in vitro acute cytotoxicity effects. (September 2022) - Meier, Philipp; Zabara, Mahsa; Hirsch, Cordula; Gogos, Alexander; Tscherrig, Dominic; Richner, Gilles; Nowack, Bernd; Wick, Peter
Graphical abstract: Textiles release particles and fibers. Here, facemasks were examined and quantified in this regard, a metallic content analysis conducted and the in vitro cytotoxicity of residues determined on lung cells. Abstract: Since the start of the current COVID-19 pandemic, for the first time a significant fraction of the world's population cover their respiratory system for an extended period with mostly medical facemasks and textile masks. This new situation raises questions about the extent of mask related debris (fibers and particles) being released and inhaled and possible adverse effects on human health. This study aimed to quantify the debris release from a textile-based facemask in comparison to a surgical mask and a reference cotton textile using both liquid and air extraction. Under liquid extractions, cotton-based textiles released up to 29′452 ± 1′996 fibers g −1 textile while synthetic textiles released up to 1′030 ± 115 fibers g −1 textile. However, when the masks were subjected to air-based extraction scenarios, only a fraction (0.1–1.1%) of this fiber amount was released. Several metals including copper (up to 40.8 ± 0.9 µg g −1 ) and iron (up to 7.0 ± 0.3 µg g −1 ) were detected in acid dissolved textiles. Additionally the acute in vitro toxicity of size-fractionated liquid extracts (below and above 0.4 µm) were assessed on human alveolar basal epithelial cells. The current study shows no acute cytotoxicity response for all the analyzed facemasks.